Rice Snail Shell Siege Machine Design - Alif Imam Utomo; Iwan Nugraha Gusniar; Iman Dirja; Eka Yulianty (VANOS Journal of Mechanical Engineering Education, 2023)
The rice field snail can be used as a processed food that can be consumed by humans because it contains protein in its meat. However, consuming rice field snails can produce waste field snail shells which are disturbing because they have an unpleasant odor if left alone. Therefore, the rice field snail shell waste is maximized to be used as poultry feed. To make it easier to make the poultry feed, this study aims to design a penepung machine to smooth the shells of rice field snails. Based on the design results using solidworks 2019 software, the design of the siege machine components consists of a driving motor with a power of 6 HP, a drive pulley with a diameter of 50.8 mm, a driven pulley with a diameter of 152.44 mm, v-bet type A with a length of 44 inches . So after testing, the design results obtained for rice field snail shells which have a capacity of 12 kg/hour with an efficiency of 42%. By using the cost of materials and manufacture of Rp. 4,034,500.